Nicollo Machiavelli’s perspective of politics - Chekaramit, Tetiana (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
In this article, the focus is on classic author Niccolo Machiavelli. Machiavelli’s work has constituted the object of research and analysis from two relatively opposite perspectives: the historical one and the moral one. The aim of the paper is to present Machiavelli’s approach for politics in this two perspectives.
Keywords: politics; Niccolo Machiavelli; theory of philosophy